2008
DOI: 10.1002/adma.200800324
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Surface‐Bound Redox‐Active Conjugated Wires Derived From Mono‐ and Dinuclear Iron(II) and Ruthenium(II) Oligo(phenyleneethynylene) Complexes

Abstract: Functional molecular materials are playing an everincreasing role in the fabrication of smart integrated devices that can perform inter alia logic operations. [1][2][3][4][5][6] As a result, the nano-engineering of molecular systems on surfaces has recently become a major focus of activity in the design and tailored construction of innovative materials. [7] The modification of conducting surfaces at the molecular level with redoxactive ''building blocks'' constitutes a powerful approach to the fabrication of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
66
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 32 publications
4
66
0
Order By: Relevance
“…3,4 In this connection, we have recently shown that complexes 1 n and 2 (Scheme 1) can be readily grafted onto Si−H surfaces through SiCC bonds. 25 Furthermore, the alkynederived monolayers obtained from 1 n 34 possess remarkably fast charge-transfer kinetics with the underlying silicon chip. 26 Due to the presence of interfacial vinyl bonds, the resulting monolayers are densely packed and are more ordered, and exhibit a higher surface coverage than alkene-derived monolayers, as previously demonstrated for purely organic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In this connection, we have recently shown that complexes 1 n and 2 (Scheme 1) can be readily grafted onto Si−H surfaces through SiCC bonds. 25 Furthermore, the alkynederived monolayers obtained from 1 n 34 possess remarkably fast charge-transfer kinetics with the underlying silicon chip. 26 Due to the presence of interfacial vinyl bonds, the resulting monolayers are densely packed and are more ordered, and exhibit a higher surface coverage than alkene-derived monolayers, as previously demonstrated for purely organic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of transition metal complexes transRuCl(C"CR)(dppe) 2 is very well established [1][2][3][4][5][6][7][8][9][10], with a considerable body of recent research demonstrating the utility of these moieties in the construction of multimetallic complexes [11][12][13][14][15], optical materials [16][17][18], including those that exhibit pH or redox-switchable NLO response [19][20][21][22][23][24][25], colormetric [26] and fluorescent [27] sensing behaviour, the ''wire-like" behaviour that arises from extensive d-p mixing along the Ru-C"C fragment [28][29][30][31][32][33][34][35][36][37], and other characteristics that make these compounds potentially useful molecular electronic components [5,33,34,[38][39][40][41]. The facile replacement of the chloride ligand in complexes trans-RuCl(C"CR)(dppe) 2 either directly or from related vinylidenes with a second alkynyl ligand is well documented …”
Section: Introductionmentioning
confidence: 99%
“…On another front, the electrochemical behaviors of redox active self-assembled monolayers (SAMs) on silicon electrodes have been investigated energetically because silicon is one of the essential semiconducting materials in the present electronics and expected as a promising electrode for molecular electronic devices [18][19][20][21][22][23][24]. The asymmetric charge transfer and the photoresponsive redox behavior have been caused by the semiconducting electronic properties such as dopant type, resistivity and band gap [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%